2019
DOI: 10.1002/jbm.b.34448
|View full text |Cite
|
Sign up to set email alerts
|

Freeze‐dry processing of three‐dimensional cell constructs for bone graft materials

Abstract: Freeze‐dry processing improves the operability and stability of cell‐based biomaterials and facilitates sterilization for clinical application. However, there is no established freeze‐drying protocol for engineered tissues. Recently, we reported that biomimetic bone tissues can be fabricated using scaffold‐free three‐dimensional (3D) cell constructs with potential applications as bone graft materials. The purpose of this study was to assess the influence of freeze drying on the morphology and components of 3D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…[ 237 ] Sucrose is a protein protectant to stabilize the protein conformation widely used in freeze/dry processing. The suppression of protein denaturation [ 238 ] by a high concentration of sucrose makes it possible to allow the bioactive molecule loading in vivo to engage in the regenerative process. Furthermore, superfluous sucrose involves glycometabolism for synthesizing myelin lipids; [ 239 ] thus, it is unnecessary to worry about spillover sucrose affecting NGC in vivo.…”
Section: The Manufacturing Technologies Applied In the Ngcmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 237 ] Sucrose is a protein protectant to stabilize the protein conformation widely used in freeze/dry processing. The suppression of protein denaturation [ 238 ] by a high concentration of sucrose makes it possible to allow the bioactive molecule loading in vivo to engage in the regenerative process. Furthermore, superfluous sucrose involves glycometabolism for synthesizing myelin lipids; [ 239 ] thus, it is unnecessary to worry about spillover sucrose affecting NGC in vivo.…”
Section: The Manufacturing Technologies Applied In the Ngcmentioning
confidence: 99%
“…However, some drawbacks of freeze‐dry processing should be of concern as well. The freeze‐dried cell body produces irregular pores [ 211 ] and inevitably changes the volume, which may influence the inorganic or organic constituent for regeneration [ 238 ] when processed with cells or growth factors.…”
Section: The Manufacturing Technologies Applied In the Ngcmentioning
confidence: 99%
“…To establish the freeze-dry protocol for 3D cell constructs as a biomimetic bone tissue, the BMSC constructs were pretreated with or without sucrose [ 83 ]. The experiments showed that the size of the BMSC construct decreased and the morphology was maintained ( Figure 8 ).…”
Section: Application Of 3d Cell Constructs For Bone Regenerative Biomaterialsmentioning
confidence: 99%
“…In contrast, 10 wt% sucrose in PBS maintained the ALP activity in the constructs. These results indicated that the freeze-dry processing of 3D cell constructs with suitable protein protectants enabled the fabrication of a novel bone substitute comprising only cells [ 83 ].
Figure 8.
…”
Section: Application Of 3d Cell Constructs For Bone Regenerative Biomaterialsmentioning
confidence: 99%
See 1 more Smart Citation